Leadership and Motivation On Employee Performance - Soraya Khadijah, Melissa (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The purpose of this research is to understand and analyze: (1) Leadership (2) work motivation; (3) Employee Performance; and (4) the influence of Leadership and work motivation on Employee Performance at Madrasah Aliyah Azzakiyah, Bandung Regency, both simultaneously and partially. The research methods used in this study are descriptive surveys and explanatory surveys, with the unit of analysis being the employees at Madrasah Aliyah Azzakiyah Bandung Regency, with a sample size of 30 people. The type of investigation is causality, and the time horizon in this study is cross-sectional. Based on the research results, it was found that Leadership at Madrasah Aliyah Azzakiyah Kabupaten Bandung received mostly positive responses from the employees; the work motivation of employees at Madrasah Aliyah Azzakiyah Bandung Regency can generally be considered good; the Employee Performance at Madrasah Aliyah Azzakiyah Kabupaten Bandung is currently rated as good. Leadership and Work Motivation simultaneously influence Employee Performance at Madrasah Aliyah Azzakiyah, Bandung Regency. However, partially, Leadership has a more dominant influence on performance than Work Motivation. Since Leadership has a more dominant influence on Performance, making it the top priority in improving Employee Performance, Madrasah Aliyah Azzakiyah Bandung Regency is expected to pay attention to the fact that leaders significantly contribute to the improvement of employee performance.